Pharmacological evaluation of nasal delivery of selegiline hydrochloride-loaded thiolated chitosan nanoparticles for the treatment of depression. (2nd April 2016) - Singh, Devendra; Rashid, Muzamil; Hallan, Supandeep Singh; Mehra, Neelesh Kumar; Prakash, Atish; Mishra, Neeraj
Abstract : The aim of the present study was to investigate the propensity of thiolated chitosan nanoparticles (TCNs) to enhance the nasal delivery of selegiline hydrochloride. TCNs were synthesized by the ionic gelation method. The particle size distribution (PDI), entrapment efficiency (EE), and zeta potential of modified chitosan (CS) nanoparticles were found to be 215 ± 34.71 nm, 70 ± 2.71%, and + 17.06 mV, respectively. The forced swim and the tail suspension tests were used to evaluate the anti-depressant activity, in which elevated immobility time was found to reduce on treatment. TCNs seem to be promising candidates for nose-to-brain delivery in the evaluation of antidepressant activity.